Photoactivation of olfactory sensory neurons does not affect action potential conduction in individual trigeminal sensory axons innervating the rodent nasal cavity - Maurer, Margot; Papotto, Nunzia; Möhrlen, Frank; Frings, Stephan; Carr, Richard (PLOS ONE, 2019)
Olfactory and trigeminal chemosensory systems reside in parallel within the mammalian nose. Psychophysical studies in people indicate that these two systems interact at a perceptual level. Trigeminal sensations of pungency mask odour perception, while olfactory stimuli can influence trigeminal signal processing tasks such as odour localization. While imaging studies indicate overlap in limbic and cortical somatosensory areas activated by nasal trigeminal and olfactory stimuli, there is also potential cross-talk at the level of the olfactory epithelium, the olfactory bulb and trigeminal brainstem. Here we explored the influence of olfactory and trigeminal signaling in the nasal cavity. A forced choice water consumption paradigm was used to ascertain whether trigeminal and olfactory stimuli could influence behaviour in mice. Mice avoided water sources surrounded by both volatile TRPV1 (cyclohexanone) and TRPA1 (allyl isothiocyanate) irritants and the aversion to cyclohexanone was mitigated when combined with a pure odorant (rose fragrance, phenylethyl alcohol, PEA). To determine whether olfactory-trigeminal interactions within the nose could potentially account for this behavioural effect we recorded from single trigeminal sensory axons innervating the nasal respiratory and olfactory epithelium using an isolated in vitro preparation. To circumvent non-specific effects of chemical stimuli, optical stimulation was used to excite olfactory sensory neurons in mice expressing channel-rhodopsin (ChR2) under the olfactory marker protein (OMP) promoter. Photoactivation of olfactory sensory neurons produced no modulation of axonal action potential conduction in individual trigeminal axons. Similarly, no evidence was found for collateral branching of trigeminal axon that might serve as a conduit for cross-talk between the olfactory and respiratory epithelium and olfactory dura mater. Using direct assessment of action potential activity in trigeminal axons we observed neither paracrine nor axon reflex mediated cross-talk between olfactory and trigeminal sensory systems in the rodent nasal cavity. Our current results suggest that olfactory sensory neurons exert minimal influence on trigeminal signals within the nasal cavity.
Gesehen am 03.12.2019